Research and Application of Vibration Monitoring Technology of Blast Furnace Top Gearbox - Lou Shiyu; Luo Dachun; Tang Zhiyong; Xie Han (Jixie chuandong)
Through picking up the signal on the blast furnace top gearbox transmission model,using wavelet technology and the envelope demodulation method,the signal analysis is carried out,the gearbox online vibration monitoring system is established. At the same time,the important function of 133 Hz characteristic frequency to the precontrol of equipment working state is put forward.